1973
DOI: 10.1021/ja00794a022
|View full text |Cite
|
Sign up to set email alerts
|

Acidity of hydrocarbons. XLVII. Primary kinetic isotope effects and internal return in hydrogen isotope exchange of toluene and triphenylmethane with lithium cyclohexylamide

Abstract: Experimental primary isotope effects for LiCHA-catalyzed proton exchange are compared for toluene and triphenylmethane. For toluene at 25°, /cDexPti/A:TexPti = 2.82 in cyclohexylamine (CHA) and fcHexPti/kTexP« = 27.2 in cyclohexylamine-W/V-if (CHA-A). For triphenylmethane at 25°, kH,.,rjtl/7cTcxpii = 2.79 in CHA and &HexPti/&Te*Pti = 19.2 in CHA-,. Derived internal return values show that internal return is greater for triphenylmethane than for toluene. Mechanistic primary isotope effects for the proton transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…It is thus concluded that whilst the formal deprotonation of toluene by 2 is thermodynamically very unfavourable, the reaction between 2 and toluene may be closer to a concerted process (pathway II , Scheme ) than a fully ionogenic process (pathway III ) to facilitate a sufficiently low activation barrier (116 kJ mol −1 ) for reaction to proceed at a reasonable rate. The magnitude of the primary and secondary deuterium isotope effects18,31 are consistent with this in that the transition state for proton transfer would be “late”. Indeed the primary KIE ( k H / k D =4.2(±0.6)) is similar in magnitude to that reported by Moss et al for the insertion of dimethoxy carbene into the OH bond of methanol ( k H / k D =3.3(±0.5),21e for which a pathway of type III (with some characteristics of II ) was suggested 21f.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is thus concluded that whilst the formal deprotonation of toluene by 2 is thermodynamically very unfavourable, the reaction between 2 and toluene may be closer to a concerted process (pathway II , Scheme ) than a fully ionogenic process (pathway III ) to facilitate a sufficiently low activation barrier (116 kJ mol −1 ) for reaction to proceed at a reasonable rate. The magnitude of the primary and secondary deuterium isotope effects18,31 are consistent with this in that the transition state for proton transfer would be “late”. Indeed the primary KIE ( k H / k D =4.2(±0.6)) is similar in magnitude to that reported by Moss et al for the insertion of dimethoxy carbene into the OH bond of methanol ( k H / k D =3.3(±0.5),21e for which a pathway of type III (with some characteristics of II ) was suggested 21f.…”
Section: Discussionmentioning
confidence: 60%
“…Deuterium labelling at the toluene methyl group ([D 8 ]‐, [D 1 ]‐ and [D 0 ]toluene) results in moderate primary and large secondary KIEs for [D 1 ]toluene in C 6 D 6 (primary ( k H / k D )=4.2(±0.6)) and secondary ( k H / k D )=1.18(±0.08)), and for [D 0 ]toluene/[D 8 ]toluene as reactant and solvent ( k H / k D =10.9±1.9 on rate and k [D 0]tol/ k [D 8]tol=9.5±0.8 for partitioning) 30. These are consistent with rate‐limiting CH cleavage (${k{{{\rm \bf II}\hfill \atop 1\hfill}}}$ or ${k{{{\rm \bf III}\hfill \atop 1\hfill}}}$ in Scheme ) proceeding via a late transition state,18 with an accompanying decrease in p character at the benzylic carbon and little competing internal return, which would reduce the primary KIE to an equilibrium isotope effect (${K{{{\rm \bf III}\hfill \atop 1\hfill}}}$ in Scheme ) 31,32. Analysis of the chemical shift of the 13 C{ 1 H} NMR signal arising from C(2) in [ 13 C 1 ]‐ 2 indicates that there is rapid and reversible complexation of carbene 2 to the (K‐HMDS) 2 with an association constant of K a =62(±6) M −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The average value, k 2 = 1.9 ± 0. 7 but the lithium amide is aggregated and only the small amount of monomer present is the active catalyst. The solvent isotope effect in that case is probably an effect on the aggregation equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation has been described previously. 7 Cesium cyclohexylamide-N-d was prepared by reaction with cesium metal. Note, however, that this reaction is much slower than the reaction of cesium metal with undeuteriated cyclohexylamine.…”
Section: Methodsmentioning
confidence: 99%
“…For personal use only. significant contribution to the exchange process of 'internal return' (31), with this being more pronounced for HZe than HZa Because of its high acidity, trifluoroacetic acid can hardly be regarded as a typical medium for the formation of a carbanion. Yet there is no doubt that hydrogen exchange of 26 takes place in the TFA-D20 mixture.…”
Section: Deprotonation Of L3-bissulfonium Saltsmentioning
confidence: 99%